Engineering Tribology and Biomedical Materials : selected peer-reviewed full text papers from the 4th PST and 2nd ICETAT - Limmatvapirat, Sontaya; Hwang, Yunn-Lin (Key engineering materials, 2021)
Selected peer-reviewed full text papers from the 4th PST and 2nd ICETAT.